Hubungan efikasi diri (self efficacy) dengan prokrastinasi akademik dalam penyelesaian skripsi pada mahasiswa - Yana Anggita Venanda (University of Merdeka Malang, 2022)
The covid 19 pandemic conditions have had a lot of impacts on the world of education, one of which has caused a delay in the final thesis hearing and led to a setback in graduation time. In psychology, deliberately delaying the completion of a task is called procrastination. Self-efficacy is viewed as one of the factors able to predict the tendency of academic procrastination. This reseacher has to understand corelation of self-efficacy and academic procrastination in the completion of thesis in students. The sample was 99 students of the Faculty of Psychology, in a private University Malang who are active in the odd semester thesis program for the academic year 2020/2021. The measuring instrument used in this study was the academic procrastination (validity of 0.308-0.638) and the self-efficacy scale (validity of 0.311-0.697). A hypothetical processed with the product moment technique and results coefficients of correlation of -0.367, p value of 0.000 (p 0.05). It means that there is a significant negative corelation between self-efficacy and academic procrastination in the completion of thesis in students. It is interpreted that the higher the level of self-efficacy in students, the lower the tendency for the emergence of academic procrastination behavior in the completion of the thesis, and vice versa. Covid 19 berdampak bagi dunia pendidikan, salah satunya penundaan pelaksaaan sidang akhir skripsi dan menyebabkan kemunduran waktu kelulusan. Dalam psikologi, sengaja menunda penyelesaian tugas akademik disebut prokrastinasi akademik. Efikasi diri dipandang sebagai salah satu faktor yang mampu memprediksi kecenderungan prokrastinasi akademik. Penelitian ini bertujuan untuk mengetahui hubungan antara efikasi diri dengan prokrastinasi akademik dalam penyelesaian skripsi pada mahasiswa. Sampel penelitian 99 mahasiswa/i Fakultas Psikologi salah satu Universitas Swasta di Kota Malang aktif program skripsi semester ganjil tahun akademik 2020/2021. Alat ukur berupa skala prokrastinasi akademik (validitas 0,308 - 0,638) dan skala efikasi diri (validitas 0,311 - 0,697). Uji hipotesa rumus product moment menghasilkan koefisien korelasi -0,367 dengan p value 0,000 (p0,05). Bermakna bahwa terdapat hubungan negatif secara signifikan antara efikasi diri dengan prokrastinasi akademik dalam penyelesaian skripsi pada mahasiswa. Diinterpretasikan semakin tinggi tingkat efikasi diri pada mahasiswa/i maka semakin rendah kecenderungan munculnya perilaku prokrastinasi akademik dalam penyelesaian skripsi, dan sebaliknya.